Why is Romania in Last Place in Europe (30 out of 30 Countries Analyzed) in the Work-Life Balance Index - Manea, Ciprian (Journal of Danubian Studies and Research, 2024)
According to a study conducted by a prestigious Institute2 in 2023, in Romania, the level of balance between work and personal life is the place out of 30 countries where these researches were carried out). The purpose of this scientific research is to identify the reason for this ranking for Romania and to identify ways to improve the indicators that determine the World-Life Balance indicator. Let’s understand what is the reason that led to this result. The research presented in the annex identified 8 indicators that could be measured to determine a ranking in Europe.